Magnification loupes influence on neck and trunk flexion of dental hygienists while scaling—A pilot study. Issue 1 (20th October 2020) - Ludwig, Emily A; Tolle, Susan L; Jenkins, Eric; Russell, Daniel
Abstract: Objective: Work‐related musculoskeletal disorders (MSDs) are common in the dental hygiene profession. Awkward postures contribute to MSDs and magnification loupes have been suggested to reduce this risk factor and minimize MSDs. Methods: After IRB approval, 24 hygienists were enrolled in the study: twelve hygienists wearing loupes with a standard manufacturer determined declination angle (control) and 12 hygienists wearing loupes with a custom measured declination angle (experimental). To measure changes in neck and trunk flexion, accelerometers were placed on the occipital region of head, cervical vertebrae C5, and thoracic vertebrae T5 and baseline posture was recorded. Typodonts with artificial calculus simulated the oral environment. Participants were randomly assigned to wear their designated loupes during the first or second trial of the experiment and scaled in each quadrant (UR, LR, UL, LL) of the mouth for two minutes. Participants completed the scaling task twice: in the loupes and no loupes condition in a counterbalanced order. Three‐way mixed design ANOVA was used to determine posture differences in neck and trunk posture. Results: Those wearing custom loupes (M = 16.52, SD = 6.40) had significantly less trunk flexion while scaling compared to hygienists wearing standard loupes (M = 22.27, SD = 6.40), F (1, 22) = 7.14, P  = .01. Neck flexion was not significantly affected while scaling between loupes vs no loupes or loupes type condition, ( P 's > .05). Conclusion: Posture was partially impacted by loupes type. Custom loupes resulted in less trunk flexion. Neck flexion was not affected by either loupes type.